THE INFLUENCE OF THE PALM SUGAR MASS ON THE MAKING OF THE COMPOS FROM THE PALM OIL SALES WITH ANAEROBIC FERMENTATION METHOD USING EM-4 - Ramli Ramli; Marlinda Marlinda (Universitas Lambung Mangkurat, 2017)
Abstract- East Kalimantan, especially Kutai regency produces 1,112,442 tons/year of palm oil. Oil palm empty fruit bunches (EFB) are one of the wastes generated in the processing of palm oil that is equal to 20-23% of the fresh fruit bunches, so the amount of EFB that can be generated is 244,737.24 tons/year. The purpose of this study is to determine the effect of palm sugar as a nutrient to nutrient nitrogen EM4, phosphor and potassium in composting EFB. This research was conducted by varying the mass of Palm Sugar: 0.4000 g, 0.6000 g, 0.8000 g, 1.0000 g and 1.2000 g. The main composting process that was carried out by adding EM4 solution of 10 mL and 100 mL sugar solution into 200 grams EFB, letting it stand for 30 days, and after that the analysis was conducted. The total content of nutrients is highest on the mass of 1.2000 g palm sugar that is 3.174%. The conclusion of this study is the greater the mass of Palm Sugar is added, the greater the concentration of nutrients found in the composting by using bacterial EM4. Keywords: bio-activator EM4, palm Sugar, EFB.